Is a Plant-Based Diet Associated with Relationship Aggression? - Taft, Casey; Franz, Molly; Hamilton, Evelyn; Smethurst, Madeline; Garza, Anissa; Padilla-Medina, Diana; Davis, Maxine (My University, 2022)
Examinations of links between plant-based diet and indices of physical and mental health have received increased attention in the scientific literature in recent years. However, there has been little to no published research examining associations between plant-based diet and use of aggressive behavior. The current study examined the link between a plant-based diet and partner aggression in a nationally representative United States sample of 1,763 individuals while controlling for childhood trauma and partner aggression victimization. Results indicated that while a plant-based diet was associated with greater use of relationship aggression at the bivariate level, this association did not remain significant when accounting for childhood trauma and aggression victimization. These results suggest the importance of considering the role of trauma and victimization when examining links between plant-based diet and aggression, and point to a number of possible avenues for additional investigation to better understand these associations.